La Renuncia anticipada, suscrita por el trabajador y presentada a trámite por el empleador, debe impedirse - Guarnizo Campoverde, Karina Elizabeth (2016)
Our labor system for many years has undergone a series of changes for better or for worse have directly affected the only force that can lead to the development of peoples, the worker. The current Constitution of the Republic of Ecuador, guarantees people the right to work, is a source of personal fulfillment and based on manifests family finances, but nothing is said about job security must go hand in hand with the sacred law, for the faithful compliance with the principles set out in labor matters. This thesis is developed in the legal field specifically on the shortcomings that exist in the Labour Code, with regard to the early resignation. Its preparation was counted with an extensive bibliography on labor law, based on doctrinaire concepts of employer, worker, resignation, labor law, historical review, and a comprehensive analytical and critical study of the rules of the Constitution of the Republic of Ecuador and the Labour Code; and also an investigation from the point of view of comparative law reinforced with field research that includes surveys and interviews applied to lawyers of our city of Loja; which they are vital for the effective regulation applicable to the early resignation, subject of this investigation, culminating in the drafting of conclusions and recommendations, as well as the proposed legal reform. The problem raised refers to the current practice made by the majority of employers, which is to have the worker sign the resignation in advance before obtaining the work, a practice that seriously violates the inalienable rights of workers, which are Enshrined in our Constitution, as well as in international treaties and labor laws of our country.